Effects of a Supply Chain Collaboration model on Competitiveness via Collaborative Advantages and Reduction of Supply Chain Disruption - Apinyaporn Sopa; Krittapha Saenchaiyathon (International Journal of Supply Chain Management, 2020)
Model of Supply chain collaboration model that affects on competitive advantage via collaboration advantage and reduction of supply chain disruption: a case study in Automotive Parts Manufacturing Industry in Thailand. The aims of this study were to investigate the mediating effects of collaboration advantage and reduce supply chain disruption on the relationship between Supply chain collaboration and competitiveness. Data were obtained from 282 manager in production division of small and medium-sized enterprises (SMEs) in automotive parts manufacturing industry in Thailand. Structural equation model (SEM) technique was employed for data analysis. The findings indicated that supply chain collaboration had significant positive effect on collaboration advantage and competitive advantage. Furthermore, collaboration advantage and reduce supply chain disruption had significant positive impact on competitiveness. On the other hand, supply chain collaboration had significant negative effect on reduce supply chain disruption. This is quite a surprising result. The discovery of the relationship between supply chain collaboration and competitive advantage in this field benefits for not only academic sector but also public and private sectors. The study suggests that organizations enable to improve their collaboration advantage, including process efficiency, offering flexibility and innovation, by developing either supply chain collaboration practices. This, in turn, enhances organizational performance in high competitive advantage.